2019
DOI: 10.1002/jia2.25336
|View full text |Cite
|
Sign up to set email alerts
|

Is knowledge of HIV status associated with sexual behaviours? A fixed effects analysis of a female sex worker cohort in urban Uganda

Abstract: Introduction Female sex workers (FSWs) have strong economic incentives for sexual risk‐taking behaviour. We test whether knowledge of HIV status affects such behaviours among FSWs. Methods We used longitudinal data from a FSW cohort in urban Uganda, which was formed as part of an HIV self‐testing trial with four months of follow‐up. Participants reported perceived knowledge of HIV status, number of clients per average working night, and consistent condom use with clients at baseline, one month, and four months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 56 publications
(103 reference statements)
1
8
0
Order By: Relevance
“…The finding that knowledge of HIV-negative status significantly increases consistent condom use with clients is consistent with the findings from a similar study among a cohort of FSWs in urban Uganda, 35 but it contradicts much of the literature among members of the general population suggesting that knowledge of HIV-negative status does not affect HIV risk-related sexual behaviors. 2,3,[6][7][8][9][10] The suggestion that knowledge of HIV-positive status might also increase consistent condom use with clients is contradictory to the findings from the similar study among the Ugandan FSW cohort (which suggest that knowledge of HIV-positive status may decrease consistent condom use with clients), 35 but it is consistent with literature among members of the general population. 1,2,4,5,7,8,10 The observed increase in consistent condom use following knowledge of HIV-negative status is encouraging, as it indicates that FSWs in this setting are incentivized to engage in behaviors that decrease their risk of HIV acquisition.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The finding that knowledge of HIV-negative status significantly increases consistent condom use with clients is consistent with the findings from a similar study among a cohort of FSWs in urban Uganda, 35 but it contradicts much of the literature among members of the general population suggesting that knowledge of HIV-negative status does not affect HIV risk-related sexual behaviors. 2,3,[6][7][8][9][10] The suggestion that knowledge of HIV-positive status might also increase consistent condom use with clients is contradictory to the findings from the similar study among the Ugandan FSW cohort (which suggest that knowledge of HIV-positive status may decrease consistent condom use with clients), 35 but it is consistent with literature among members of the general population. 1,2,4,5,7,8,10 The observed increase in consistent condom use following knowledge of HIV-negative status is encouraging, as it indicates that FSWs in this setting are incentivized to engage in behaviors that decrease their risk of HIV acquisition.…”
Section: Discussionsupporting
confidence: 76%
“…This measurement approach has previously been used in other studies, including a similar study among FSWs in Uganda. 35 Our measurement of knowledge of HIV status in this study is participants' perceived knowledge of HIV status, which may not reflect participants' most recent HIV test result. Among our study participants, perceived HIV status may differ from actual HIV status for reasons including a new HIV risk encounter after recent HIV testing, mistrust of a new HIV testing technology (e.g., self-testing), and participation in an intervention believed to cure HIV infection (e.g., religious ceremony).…”
Section: Exposure: Knowledge Of Hiv Statusmentioning
confidence: 98%
See 1 more Smart Citation
“…Learning one’s HIV status, whether positive or negative, can be an empowering process, but can also require a fundamental reshaping of one’s social identity. In a population at high HIV risk (such as FSWs in Sub-Saharan Africa), a majority will still test HIV-negative, despite subjective assumptions to the contrary ( Ortblad et al, 2019 ). In the present study, participants expressed fatalism regarding the inevitability of an HIV infection during the baseline interviews, but also surprise and reassurance following a (unexpected) negative test result at follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are largely consistent with HIVST research in Uganda. Quantitative research with the same cohort of FSWs found that learning one's HIV status led to decreases in the severity of depressive symptoms (Ortblad et al, 2020) and knowledge of an HIVnegative status led to increases in condom use (Ortblad et al, 2019), both factors that may be at least partially explained by the qualitative data showing that HIVST sparked feelings of self-worth, and a desire to live healthy, full lives (Wachinger et al, 2020). A qualitative study among FSWs in Rakai, Uganda, which preempted the distribution of HIVST kits, found that FSWs perceived HIVST as advantageous because it bolsters privacy and convenience, but problematic because it circumvents formal counseling, which is echoed in our data stemming from actual experience (Burke et al, 2017).…”
Section: Discussionmentioning
confidence: 99%